Introduction to the Special Issue on Clostridioides difficile Infection, Second Edition - Guido Granata (MDPI AG, 2024)
Clostridioides difficile (CD) is a Gram-positive, anaerobic bacterium that is one of the most common causes of infective diarrhoea worldwide [...]